2008
DOI: 10.1007/s10290-008-0149-9
|View full text |Cite
|
Sign up to set email alerts
|

Inflation Expectations and Inflation Uncertainty in the Eurozone: Evidence from Survey Data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 8 publications
1
23
1
Order By: Relevance
“…In this context, the question arises of whether the economic policy of the euro area can successfully reduce the uncertainty by a similar proportion across countries. In a way this also relates to the conjecture of Arnold and Lemmen (2008) that, within the euro area, "inflation uncertainty may increase in countries that have a smaller influence on ECB policy. "…”
Section: Introductionmentioning
confidence: 85%
“…In this context, the question arises of whether the economic policy of the euro area can successfully reduce the uncertainty by a similar proportion across countries. In a way this also relates to the conjecture of Arnold and Lemmen (2008) that, within the euro area, "inflation uncertainty may increase in countries that have a smaller influence on ECB policy. "…”
Section: Introductionmentioning
confidence: 85%
“…Evidence from empirical research reported so far remains mixed. On the one hand, Arnold and Lemmen (2006) found stronger dependence of inflation expectations on country-specific past inflation rates than euro-area inflation target. On the other hand, Hofmann and Remsperger (2005) find that other countries' real interest rates may matter directly for one state's output gap and von Hagen and Hofmann (2004) find a significant role of the EMU-wide (and not country-specific) ex post real interest rate in countries' backward-looking IS curves.…”
Section: Real Interest Rate Channelmentioning
confidence: 92%
“…The most frequently used method is the Carlson -Parkin (CP) approach (see e.g. Carlson and Parkin (1975) for a detailed description or Forsells and Kenny (2004) and Arnold and Lemmen (2008) for relatively recent empirical applications). 2 However, the CP method is being subjected to strong criticism due to its heavy reliance on unrealistic and over-restrictive theoretical assumptions.…”
Section: Consumer Survey Methodologymentioning
confidence: 99%
“…However, Mankiw et al (2003) disqualify this kind of indicator as a reasonable proxy for inflation uncertainty, regarding it as a mere measure of disagreement between forecasters. In order to circumvent this shortcoming, the approach suggested by Arnold and Lemmen (2008) is followed here.…”
Section: Consumer Survey Methodologymentioning
confidence: 99%
See 1 more Smart Citation